JEJAK BAHASA JAWA SAMIN KLOPODUWUR BLORA (Sebuah Rekaman Sinkronis) - Indrariani, Eva Ardiana (SASINDO, 2013)
Linguists noted people in the region Blora have unique Javanese tradition still maintained until now,namely "Samin Language". This tradition first emerged as a community effort to protect themselves andresist passively against invaders. The fact the field indicates that Samin community no longer exists in thelocation of the early occurrence of Samin learning in Klopoduwur village, subdistrict Banjarejo, Blora.This paper tried to trace the footprints of Samin Java language in the remaining families in the region.Data collected through observation of the recording technique, see, and record, as well as throughquestionnaires. Analysis of data using a qualitative approach and performed with frontier methods.Based on the results of research can be said that there are some differences and similarities between theJava language of descent Samin families (BJKKS) with standard Java language, ie, there are 25differences and 92 similarities. BJKKS also have a variation in a phonological, morphological, andlexical. The differences are minimal and do not show peculiarities Samin style. It proves that BJKKS notmuch different from the standard Java language. Therefore, it can be said that the trail of uniquenessSamin language in Klopoduwur Blora has been lost over the loss of community.Key Words: Javanese, Samin, Klopoduwur Blora, Lost